Through Biotechnology... Overcoming complexities in coconut improvement - Karun, Anitha; Rajesh, M K; Chowdappa, P (Indian Horticulture, 2018)
Given the long duration and heterozygous nature of coconut palm, applicationof traditional breeding techniques are cumbersome and time consuming incoconut. There exists a tremendous potential for utilization of biotechnologicaltools for improvement of coconum especially in the areas of embryo culturefor safe germplasm exchange, cryopreservation for conservation ofgermplasm and molecular markers for diversity studies and hybridauthentication.